POTENSI WAKAF DAN PENGELOLAAN DI BENGKULU - Hak, Nurul (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2018)
Waqf management as demanded by law still has to be questioned, Bengkulu is one of the regions that has extensive waqf, but its management is not in accordance with the law. The potential of waqf in Bengkulu is very large, which is 375,743.1 M2 spread over 290 locations in 9 District in Bengkulu City. From a number of waqf generally used for mosques, prayer rooms, boarding schools, madrasas and tombs. The management pattern is still traditional and unproductive, this is because of the understanding of endowments dominated by classical fiqh, while understanding the law is still lacking. The ability of the waqf nadzir is also the cause of traditional management patterns.